2016
DOI: 10.11604/pamj.2016.24.112.7805
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of suicide attempts among Moroccan children

Abstract: Suicidal behavior among children has significantly increased in Morocco. We conducted a study on the epidemiological aspect to propose a treatment strategy. Descriptive retrospective study over a period of 3 years (April 2012-April 2015) involving children who visited pediatric medical emergencies of the Children Hospital of Rabat after an autolysis attempt. We observed epidemiological parameters, history, social and family context, the means used, the presumed cause, clinical manifestation, and the management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Our findings about the location of drug poisoning indicated it occurred more often in urban areas, which is in alignment with other studies [ 7 , 8 , 16 , 17 ], but the frequency of overdose in rural areas is not negligible (40%). This distribution is likely because the majority of the rural population use traditional medications, so pharmaceutic drugs are less present and even avoided.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings about the location of drug poisoning indicated it occurred more often in urban areas, which is in alignment with other studies [ 7 , 8 , 16 , 17 ], but the frequency of overdose in rural areas is not negligible (40%). This distribution is likely because the majority of the rural population use traditional medications, so pharmaceutic drugs are less present and even avoided.…”
Section: Discussionsupporting
confidence: 92%
“…We identified that a high proportion (91.1%) of intentional poisoning cases involved females, which contrasts with a frequency of 52.3% reported in a national study [ 8 ]. Many studies [ 12 14 , 16 ] have reported that drugs are being used in deliberate self-harming and in suicide attempts. Previous national studies found a transition in products used in acute poisoning, whereby drugs are increasingly being used in suicide attempts instead of the more traditional products such as paraphenylenediamine and toxic plants [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a psychiatric disorder multiplies by a factor of 11 to 27 the risk of suicidal attempt over the general population. [ 21 ] In our study, around half of the children had mental health issues. Out of these, a third accounted for depression, making them extremely susceptible to suicidal attempts.…”
Section: Discussionmentioning
confidence: 77%
“…In this regard, the literature shows that dysfunctional families, family conflict, and parents who use alcohol and other drugs are associated with suicidal behavior in children. 21,22 Conflicts between parents and children appear to be a major precipitating factor for children and more frequent compared to adolescents. 2 as was found in the present study.…”
Section: Discussionmentioning
confidence: 99%